The Broadband Futures Forum: The Rise of 5G and the NBN - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2021)
On 25 May 2021, TelSoc hosted the seventh Broadband Futures Forum, held online, to examine the relationship between 5G and Australia’s National Broadband Network (NBN). Two speakers discussed opportunities arising from the 5G core architecture for service creation and delivery via the NBN. Several 5G-related services that could be offered by the NBN to be used by its retail service providers were outlined. Discussion following the speeches included questions about potential service characteristics, possibilities for automation, and deployment scenarios.